Acceptance of SPARING Technology Extending TAM with Perceptions of New Technology Applied in PT.XYZ - Septian; Alizar Hasan; Reinny Patrisina (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
The application of technology has proven able to streamline operational activities in the manufacturing industry, from the receipt of raw materials to the delivery of products, as well as the control of waste generated, particularly in wastewater treatment. The continuous online wastewater monitoring system (SPARING) has become an innovation in the manufacturing industry. An analysis is needed on the level of acceptance of SPARING technology in the wastewater treatment plant division. The research aims to analyse the influencing factors of behavioral intention to use SPARING technology and to provide recommendations for addressing the most influential factors. The study employs a questionnaire method using research variables identified from a combination of the Technology Acceptance Model (TAM). The data collection process involved 36 respondents. Contribution to Sustainable Development Goals (SDGs):SDG 6: Clean Water and SanitationSDG 9: Industry, Innovation, and InfrastructureSDG 12: Responsible Consumption and ProductionSDG 13: Climate Action